(untitled) (The Indian Journal of Animal Reproduction, 2025)
Worthy Vice Chancellor, the chief guest of the function inaugurated the convention along with Dr. Gursharanjit Singh Bedi, Director of Animal Husbandry, Punjab, who graced the occasion as the Guest of Honour. The inaugural session set the tone for the three-day event, which prom ised to be a significant platform for knowledge exchange and collaboration in the field of animal reproduction. The function was presided over by Dr. Shiv Prasad, President, ISSAR and the report of society was presented by DR. M. Selvaraju, General Secretary of ISSAR. Dr. Gill high lighted the contribution of the university in uplifting the livestock sector and shared that the symposium shall play a crucial role in fostering collaboration among veterinari ans, researchers, and industry professionals to address the challenges in enhancing reproductive efficiency in live stock. He emphasized the need to provide practical solu tions that can help in improving livestock reproduction, health and productivity. The president of ISSAR, Dr. Shiv Prasad, highlighted the role of reproductive scientists in the development of health and wealth. Dr. M. Selvaraju, The 39th Annual Convention of the Indian Society for the Study of Animal Reproduction (ISSAR) and the National Symposium on “Challenges in Enhancing Reproductive Efficiency of Livestock: An Indian Perspective” was inaugurated on November 29th at 9.30am at Pal Auditorium, Punjab Agricultural University, Ludhiana, the parent university of Guru Angad Dev Veterinary and Animal Sciences University, Ludhiana. The Chairman of Convention, Dr. Sarvpreet Singh Ghuman, Dean, College of Veterinary Science (Ludhiana) and Organizing Secretary of ISSARCON-2024 and Principal Scientist cum Head, Department of Veterinary Gynaecology and Obstetrics, Dr. Mrigank Honparkhe, welcomed the gathering and guests of the function. Dr. Jatinder Paul Singh Gill, General Secretary, shared the contribution of the society in improving reproductive health of livestock. The com pendium of the lead papers and scientific abstracts was released by the dignitaries during the inaugural func tion. Dr. Mrigank Honparkhe, Organizing Secretary of the event informed that a total of 416 registrations were done by professionals, Academicians, Research Scientists, Field Veterinarians, Post graduate students, retired vets and personnel from industry. A total of 379 scientists abstracts were received for the convention. Various awards of the society as announced by Dr. M. Selvaraju, General Secretary of the society were conferred upon to various stalwarts and scientists during the inaugural function. The details of the awards are as below: